THE IMPACT OF MATERIALS MANAGEMENT ON WASTE MINIMIZATION ON GHANAIAN CONSTRUCTION SITES IN THE VOLTA AND OTI REGIONS OF GHANA - Bentum Mensah, Frank; Tsotorvor, Godfred; Kodwo Fordjour, Francis; Tsorgali, Engr. Michael (International Journal of Scientific Research and Management (IJSRM), 2023)
Minimizing of waste of materials on the construction sites contributes greatly to the general cost of the building as a result of improper supervision on sites towards storage, handling and usage of materials. However, the cost of providing building materials required to complete any construction project is greatly high perhaps amounting to 55%-60% of the tender figure. The research was aimed at ensuring effective and efficient storage and handling of construction materials at construction sites in Volta and Oti Regions to ensure waste minimization harnessed with the needed productivity, in relation to construction material management.  To effectively carry out this project, a survey method through the use of techniques such as questionnaire, observation and interviews were undertaken to actually determine what took place on the construction site in terms of material management thus, storage and handling on construction sites. Population for the study covered 25 construction companies in both Volta and Oti Regions. Quota sampling technique was adopted to distribute questionnaires to 200 respondents and stratified random sampling techniques for selection of 50 operatives on sites visited. Furthermore, interviews were carried out for 15 interviewees and also observed 35 operatives. The method used to analyze the data was descriptive statistics in percentiles through the use of tables and charts. The results showed that, building materials are not properly kept, space allocated for material storage was not enough, poor mode of material transport to site and lack of keeping adequate records among few. It is hereby recommended that Contractors, Site Supervisors and Storekeepers in the construction industries needed to be given sufficient education on the technical knowhow of material storage and handling on site. Prompt delivery of material on sites, good documentations and transport of materials, coupled with proper supervision during batching and mixing of building materials, and finally, appropriate Site layout plans mostly showing location of building and also space allocated for material storage should be applied on most Ghanaian construction.